Inca Garcilaso de la Vega in the work of Francisco González Gamarra - Sebastián Lozano, Pablo (Mercurio Peruano, 2016)
In the fourth centenary of the publication of the Royal Commentaries, the international community has recognized the symbolic nature of Inca Garcilaso not only for the Peruvian culture but for all Latin America and the world. The mestizo face of Inca Garcilaso created by Francisco González Gamarra has been recognized, in turn, by the same community as the most aesthetic and credible representation of his image. In some ways the Internet has made it possible not only the consensus of global culture on the mestizo image of Inca Garcilaso de González Gamarra, but it has made, in an unpredictable direction in the artist’s life, his desire to multiply the visual image of the Inca, as a tribute an recognition to the first Peruvian humanist.